Resposta de germoplasmas de Coffea arabica L. a benzil adenina e giberelina - Sondahl, M.R.; Monaco, L.C.; Fazuoli, L.C.; Medina Filho, H.P.; Lima, M.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The present work was carried out in an attempt to explain variable results obtained in photoperiodic studies in Coffea arabica. Seedings progenies of “Catuaí amarelo' and “Acaiá” and three hybrids between “Mundo Nova” and germplasms from Tanzania and India were grown under normal and long photoperiod (18 hours) conditions. Additional treatments with gibberellic acid and benzyladenine were made of both photoperiods. Differences were noted in the reactions of the germplasms to the photoperiods and to the treatments with both gibberellic acid and benzyladenine. “ Catuaí amarelo '' showed no differential response to photoperiod but “Abaiá'' more than dobbled growth and internode number after nine months. The hybrid progenies showed better growth and earlier lateral branches production. The results indicated the need for an adequate identification of the germplasm in photoperiod studies. It is considered that similar responses in photoperiod are to be observed in flowering control.